Determinants of E-government Readiness : An Application of Canonical Correlation and SEM Analysis Techniques - Yunis, Manal M. (2009)
E-government represents more than a diffusion of some technology in the public sector. Rather, e-government, along with the set of its accompanying operations, can promote important changes resulting in more streamlined operations and better citizen-oriented services. Previous research was mainly concerned with providing conceptual models of egovernment measures, with relatively few studies empirically investigating e-government initiatives using cross-country analysis. Based on secondary data derived from UNPAN and the World Bank, a socio-technical perspective will be applied in this paper in order to present a more comprehensive model and empirically investigate the role that social, technological, and economic factors play in the enhancement of countries‟ e-government readiness. To this end, structured equation modeling is applied. The results show that infrastructure, human capital, and the level of online presence and interactive services initiated by the government are signifi...